Pengembangan Sistem Informasi Akuntansi Kios Ikan Laut berbasis Web dan Mobile - Ridho Saputra; Silvana Rasio Henim; Anggy Trisnadoli (Journal of Applied Computer Science and Technology, 2022)
Buyung Fitri's sea fish stand is a trading business that provides fresh sea fish which it operates in the Senapelan, Pekanbaru. This stand is capable of handling wholesale and retail sales. The absence of financial records that should be required in the trading business is a problem for the stand’s owner. Therefore, a recommendation solution is given to the owner to build a website system. This system can manage transactions that occur in the sea fish business to become financial reports. This system is build based on a website using the PHP CodeIgniter framework and MySQL. In addition, this study also built a mobile app that is used to view financial reports needed by users later. Based on black box testing, it can be concluded that both systems can run well. Then based on performance testing, it can be concluded that the website system built can be accessed quickly. While the android system has low memory usage so it can run well.